USE EFFECTIVENESS OF DOSAGE AND APPLICATION TIME MOL OF BAMBOO SHOOT ON GROWTH AND RESULT CUCUMBER PLANTS (Cucumis sativus L) - Fransisko, Eko; Heriyanto, Heriyanto; Astita (Corolla International Conference, 2022)
Cucumber plant (Cucumis sativus L) is one of the fruit vegetable plants belonging to the pumpkin tribe or Cucurbitaceae. Cucumber production in Indonesia according to the Horticultural Production Statistics data of the Ministry of Agriculture (2014) is still very low, at 477,976 tons with a harvested area of 48,578 hectares or only 9.84 tons per hectare. Efforts that can be made to increase the productivity of cucumber commodities are by improving soil fertility by utilizing the available organic material resources around us, as well as providing growth hormones that can stimulate the growth and yield of cucumbers, one of the organic material resources is in the form of MOL (Juwita, M. et al., 2012).This research was conducted from June 2018 to September 2018, in Simpang Nangka Village, Selupu Rejang District, Rejang Lebong Regency, with an altitude of 968.31 M above sea level (BPS, 2014). The experimental design in this study used a Completely Randomized Block Design (RAKL), consisting of 2 factors, namely the MOL dosage and application time, each consisting of 4 and 3 treatment levels.The dosage of MOL for bamboo shoots has a significant effect on all observational variables, this indicates that the dose treatment for bamboo shoots MOL can have a good impact on being used as an ingredient to add soil nutrients to support the growth and yield of cucumber plants. The time of application of Bamboo shoots MOL had a significant effect on plant height, number of leaves, number of productive branches, fruit length per plant, and fruit weight per plant and showed no significant effect on fruit number and fruit diameter. It is suspected that the time of application of Bamboo shoots MOL are less effective for use in the generative phase, but good for use in the vegetative phase.